2017
DOI: 10.1111/os.12287
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Combined with Topical Administration of Tranexamic Acid in Primary Total Hip Arthroplasty: A Randomized Controlled Trial

Abstract: The combined administration of i.v. and topical TXA resulted in a clinically relevant reduction in blood loss, compared with placebo group. No thromboembolic complications were observed. This randomized controlled trial supports the combined i.v. and topical administration of TXA in primary THA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 39 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…The method of anaesthesia was decided by anaesthetists. To reduce bleeding, a preoperative dose of 15 mg/kg tranexamic acid (TXA) was applied intravenously before incision, and another 1 g TXA was given topically (Nakamura et al., 2014; Zeng et al, 2017). All patients received local infiltration analgesia based on a ropivacaine‐based cocktail (100 ml containing 200 mg ropivacaine, 0.5 mg epinephrine and 0.9% normal saline).…”
Section: Methodsmentioning
confidence: 99%
“…The method of anaesthesia was decided by anaesthetists. To reduce bleeding, a preoperative dose of 15 mg/kg tranexamic acid (TXA) was applied intravenously before incision, and another 1 g TXA was given topically (Nakamura et al., 2014; Zeng et al, 2017). All patients received local infiltration analgesia based on a ropivacaine‐based cocktail (100 ml containing 200 mg ropivacaine, 0.5 mg epinephrine and 0.9% normal saline).…”
Section: Methodsmentioning
confidence: 99%
“…The inhibition of local fibrinolytic activity helps prevent fibrin clot dissolution and increases its volume and strength at the raw surgical surfaces, enhancing microvascular hemostasis [44]. In addition, TXA has lower systemic absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Poeran et al [26] conducted a retrospective study of 870,000 patients with complete hip/knee replacement for 6 consecutive years in 510 hospitals in the United States, finding that the incidence of deep venous thrombosis after using TXA was 0.4%, while the incidence was 0.5% in the group not using TXA. In addition, the majority of publications showed that TXA has an acceptable safety profile without increased risk of VTE [12,[27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%